Motivation Contagion When Instructing Obese Individuals: A Test in Exercise Settings - Ng, J.; Thøgersen-Ntoumani, Cecilie; Ntoumanis, Nikos (Human Kinetics, 2012)
We examined motivation contagion in a hypothetical exercise setting. Exercise science students (n = 164) were provided with quotes of hypothetical male and female obese exercisers displaying different quality of motivation to start an exercise program. We used a 3 (exerciser motivation) × 2 (exerciser gender) × 2 (student gender) between-subjects experimental design to examine students’ (a) motivation to instruct, (b) interpersonal style, (c) perception of barrier efficacy of the exerciser, and (d) effort to identify factors that could maximize the effectiveness of an exercise program for the exerciser. Results showed that students displayed less controlled motivation and rated the exerciser as more capable of overcoming barriers to exercise when they perceived the exerciser to be autonomously motivated. However, students, particularly females, reported more autonomy support and invested more effort toward female exercisers with controlled motivation. Our findings indicate that motivation contagion effects are plausible in exercise settings and may affect interactions between fitness instructors and obese clients.